Monetary Policy with Persistent Supply Shocks - Galo Nu\~no; Philipp Renner; Simon Scheidegger (CESifo GmbH, 2024)
This paper studies monetary policy in a New Keynesian model with persistent supply shocks, that is, sustained increases in production costs due to factors such as wars or geopolitical fragmentation. First, we demonstrate that Taylor rules fail to stabilize long-term inflation due to endogenous shifts in the natural interest rate. Second, we analyze optimal policy responses under discretion and commitment. Under discretion, a systematic inflationary bias emerges when the shock impacts the economy. Under commitment, the optimal policy adopts a lean-against-the-wind approach without compensating for past inflation, implying that "bygones are bygones". We further extend the model to incorporate the zero lower bound (ZLB) and show that the optimal policy supports preemptive easing.
Keywords: E32; E58; E63; 330; deep learning; Markov switching model; cost-push shocks